Hysteresis loop analysis of gas metal arc welded ferritic stainless steel plate - Gupta S.K.; Raja A.R.; Vashista M.; Yusufzai M.Z.K. (My University, 2025)
Non-destructive testing possess more advantages over destructive testing. In this work, the change in the hysteresis loop characteristics such as average permeability, maximum flux density (MFD), remanence, coercivity and core loss were investigated in the low frequency range (frequency < 1 Hz) as well as high frequency range (frequency > 1 Hz) at different regions of gas metal arc welded ferritic stainless (FS) steel plate (base metal, heat affected zone and weld metal). Also, metallographic study and microhardness testing of all three regions have been carried out to investigate the correlation between the microstructure and the magnetic response at different magnetizing frequencies. It was observed that average permeability and maximum flux density (MFD) of all regions of the welded plate respond inversely proportional to the magnetizing frequency in both frequency ranges. Whereas, coercivity shows a proportional response to the magnetizing frequency. In low-frequency range, remanence and core loss show inverse proportional relation with the magnetizing frequency except at 0.20 Hz. Whereas, the response of remanence and core loss in the high-frequency range is irregular. © 2019 IOP Publishing Ltd.